Studi Keragaman dan Habitat Gastropoda di Daerah Litoral Muara Sungai Ketahun Bengkulu Utara - Lilis Alifah; Bhakti Karyadi; Deni Parlindungan; Aprina Defianti; Annisa Novianti Taufik; Sutarno Sutarno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to identify the abundance, diversity, dominance and evenness of gastropods at the mouth of the Ketahun River, North Bengkulu. The method used is the